Learning through slogans and headlines : a critical analysis of the National Courtesy campaigns. - Tasneem Mohamed Hussein Topiwala. (2009)
This study has two major objectives. The first is to find out if slogans used in campaigns, especially the National Courtesy Campaigns, are effective in communicating the objectives of the campaign to the target audience. Secondly, it gathers the opinions and ideas of four individuals through a series of narratives, and attempts to find out if the courtesy campaign over the past 18 years have been successful, and if they have not been, to try and analyze why. This thesis also puts forward various suggestions as to how the Courtesy Campaign can be improved in the coming years. What emerged from the narratives was a dialogic. It has been found that the slogans used in the Courtesy Campaigns from 1979 to 1996 on their own have not been effective in getting the message across to the target audience, due to many reasons. Firstly, both the objectives and the target audience have not been well-defined, and have been too broad to be able to use one slogan that appeals to everyone. One slogan does not fit all. Secondly, there could be the unfortunate effect of "campaign overkill," such that Singaporeans no longer pay any positive attention to government-run campaigns, and the slogans attached to them. Most interestingly, it could be that Singaporeans do not see themselves, or the people around them as discourteous7 to warrant the need for a courtesy campaign. Moreover, adult Singaporeans probably have more important, tangible things to wony about. They probably do not see the social, practical or economic benefits of being more courteous than they already are. Thus, the campaign might just be using the wrong appeal to attract the attention and gain the cooperation of the target audience.